Impact of Different Packaging Systems on Selected Antioxidant Properties of Frozen-Stored Cauliflower (Brassica oleracea L. var. botrytis) - Kapusta-Duch Joanna; Leszczyńska Teresa; Borczak Barbara; Florkiewicz Adam; Załubska Anna (Polish Journal of Food and Nutrition Sciences)
Brassica vegetables, including cauliflower, are characterized by a high number of valuable metabolites, which act effectively in the cancer chemoprevention, as was already revealed by several studies. This work investigates the effect of the type of container: low density polyethylene (PE-LD) packages and oriented polystyrene (OPS) packages on selected quality parameters in frozen cauliflower. The vegetable was subjected to blanching, freezing and 3 months of storage. At every stage of the experiment, the material was examined in terms of: dry matter, vitamin C, total polyphenols content, and antioxidant activity. Statistical analysis proved that the type of container had no considerable effect on the levels of the aforementioned constituents and antioxidant activity in the freeze-stored vegetables.